Restricción a la libertad personal por autoridades de policia ¿mecanismo de , proteccion de derechos humanos? el , caso del municipio de muzo- boyaca (2020)
With the promulgation of the new code of the N ational Poli ce for coexistence (law 1801 from 2016) resurge a debate o ver the faculties that have been given to the Police Authorities related with the function and prevention of crimes and the protection of human life established in the Articles 2nd and 218th of the 1991 constitution in fulfillment of wich they could restrict people's personal freedom in the cases where for established reasons by the code of rules. In the past under the validity of the mentioned code of rules of the Police (resolution 1355 of 1970) this kind of measurement where declared unconstitutional by the Supreme Constitutional Court for considering that they infringed the principal of Judicial reserve and they resulted desproporcionate to the objective pursued. Recently the sentence (C-281 of June 13, 2017) of the Constitutional Court introduced a change of the juridisprudencial line when it appointed that what was prepared by the code of rules only could apply in the municipalities that counted with the adequate places of attention and protection of all people that had been moved. The análisis of the theme identifying the way the police authority restrics people's personal freedom is infringed or protects the human rights of the habitants ofMuzo's municipality.